QUALITY OF LIFE OF THE POPULATION IN THE EYES OF THE ORGANIZER OF HEALTH CARE - Данцигер, Дмитрий Григорьевич; Филимонов, Сергей Николаевич; Андриевский, Борис Павлович; Часовников, Константин Викторович (Medicine in Kuzbass, 2022)
The article for the first time gives the concept of «quality of the population» for a comprehensive assessment of the state of health of the population in modern conditions. The quality of the population is a category that characterizes it as a subject of social life, social relations, the ability of the population to respond to the prevailing natural, technical, economic, sociocultural conditions and adapt to changing needs.
Keywords: public health and healthcare; public health protection; the quality of life of the population